Análisis de los trabajos prácticos de química general en un primer curso de universidad - Insausti, M. J. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1997)
Learning in the laboratory has been and still is a highly controversial issue among science educators although there are not many studies carried out in Spanish Universities. This paper reports an evaluation of the cunent situation in a Laboratory of General Chemistry. For the purpose of this research, a model of learning has been adopted and an evaluation of students attitude towards the Practical Works has been made.